Teacher Testing, Teacher Education, and Teacher Characteristics - Angrist, Joshua D; Guryan, Jonathan (American Economic Review, 2004)
School officials and legislators have long been concerned with the possibility of declining teacher quality (see e.g., Sean Corcoran et al., 2002). Beginning in the 1960's, states began testing prospective teachers in a direct effort to ensure that teachers meet minimum standards for basic skills and subject knowledge. By 1999, 41 states required applicants to pass some sort of standardized certification test. As a theoretical matter, however, the impact of such testing is ambiguous. Test requirements may establish a minimum achievement standard, as their proponents hope. On the other hand, testing and other certification requirements may deter some qualified applicants from teaching if these requirements are perceived as costly. This is the barriers-to-entry story first noted in the occupational licensing context by Milton F. Friedman and Simon Kuznets (1945). Another concern with job applicant testing is the possibility of an adverse impact on minority candidates, who usually do worse on tests (see David Autor and David Scarborough [2003] for a recent study). Paralleling increased state involvement in teacher certification is the increase in teachers' educational credentials, especially in public schools. For example, in 1971, over two-thirds of public-school teachers had a B.A., while only 27 percent had a master's or education specialist's degree. By 1991, however, over half of public school teachers (52.6 percent) had a master's or education specialist's degree. In contrast, the proportion of private-school teachers